A race against time: a critical analysis of elite student-athletes` accelerated temporality through story completion - Mateu, P.; Devís-Devís, J.; Torregrossa, M.; Marques, R. F. R. (International Review for the Sociology of Sport, 2024)
Numerous elite student-athletes (ESA) engaged in a dual career, balancing athletic pursuits with education, find themselves grappling with the perception of insufficient time to fulfil their demands. Existing research advocates for the implementation of programs promoting academic flexibility, alongside measures aimed at achieving balance between academic and sport-related activities. Other studies underscore the significance of equipping ESA with skills such as time management. Nonetheless, challenges persist in balancing the escalating demands of sports and education. Drawing upon Hartmut Rosa's theory of social acceleration, this study aims to analyse how ESA perceive and respond to time pressure. Employing the story completion method, data was gathered from seven ESA who crafted narratives in response to three story stems. Through reflexive thematic analysis, two overarching themes were identified: (1) no time to waste; and (2) it is what it is. ESA faced incessant pressure to optimise their time and performance and resorted to instrumentalising personal relationships, using them as a tool for career development. Nevertheless, this pressure was not universally perceived as oppressive; rather, it was often accepted as an inherent aspect of their reality. Our conclusion is that as long as capitalist societies and their accelerating impositions persist, any assistance that can be provided to ESA will inherently be limited.